Stufenmodell oder Leistungspunkte? Die Vergabe besonderer Leistungsbezüge an deutschen Universitäten - Pia Lünstroth (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2009)
One of the main issues of the reform regarding a professor's remuneration at German universities is the introduction of a performance-dependent salary. This paper applies relative rank order tournaments to special performance benefits at university level. It turns out that the awarding procedure can be categorized as different tournament types: the Stufen-Modell (level-model) is characterized as a U-type tournament and the Leistungspunkte-Modell (merit points-model) is described as a J-type tournament. Finally, procedures at 60 public-financed German universities are analyzed and compared to the explanations offered by tournament theory.
Keywords: J33; M52; I23; 330; Reform der Professorenbesoldung; U-Typ und J-Typ-Turnier